Organizational Resilience Development Model - Irdiyansah, Iyan; Sintesa, Nika; Fitri, Euis Nessia; Hidayat, Dahlan; Kasih, Arisanti Muara (Manunggal Halim Jaya, 2025)
This study aims to develop a model to strengthen organizational resilience in the form of a constellation model of variables, along with its mathematical model, which was identified in the field through an initial preliminary survey and interviews with pre-selected informants. The unit of analysis is LP3I Polytechnic Jakarta, involving 30 lecturers as informants and interviews with 11 campus heads to determine the research constellation identified in the field. The study will also uncover strategies and methods to enhance organizational resilience. From this model, research hypotheses are derived, which will be tested using path analysis during the quantitative research phase. The research begins with interviews with informants considered competent and recognized as experts in providing the expected responses. Subsequently, data reduction, data coding, data presentation, data analysis, and conclusion drawing are conducted. The research is carried out at LP3I Polytechnic Jakarta during the period of December to January 2025. The study identified several variables that are presumed to have a positive and dominant influence on organizational resilience, namely visionary leadership, knowledge management, empowerment, professional commitment, and trust as an intervening variable